Side Effects of IGR Cyromazine on Nasonia vitripennis (Hymenoptera: Pteromalidae), a Parasitic Wasp of House Fly Pupae - B Vazirianzadeh; NAC Kidd; SA Moravvej (Journal of Arthropod-Borne Diseases, 2008)
Background: Combination of cyromazine as an Insect Growth Regulator (IGR) and Nasonia vitripennis (Hymenop¬tera: Pteromalidae) a parasitic wasp may be an effective tool for reducing the house-fly populations in poultry houses and livestock farms. This study was conducted to assess the side effects of the IGR cyromazine on the level of parasit¬ism and numbers and the longevity of emerged N. vitripennis parasitoids from house fly pupae. Methods: Cyromazine treated cloth target was used as the contaminating method of the parasitoids which was ap¬plied in this research study. Results: The Weibull distribution showed that there was no significant difference among controls and cyromazine treated targets for longevity data. There was no significant effect of cyromazine on the level of parasitism of N. vitripennis using 2 test. One-way ANOVA showed that the actual numbers emerging were significantly higher in the control than in two cyromazine treatments; however, it is a useful phenomenon because of reducing the hyperparasitism. Conclusion: There is a good consistency between using N. vitripennis and 1.1% or 0.9% cyromazine treated targets. There¬fore cyromazine treated targets can be applied as a safe delivery vehicle for applying the cyromazine IGR in the poultry houses and livestock farms in an Integrated Pest Management (IPM) program.